1989
DOI: 10.1016/0031-9384(89)90296-5
|View full text |Cite
|
Sign up to set email alerts
|

Plasma catecholamine and corticosterone responses to predictable and unpredictable noise stress in rats

Abstract: Plasma noradrenaline (NA), adrenaline (A) and corticosterone (CS) increases were determined in individual rats subjected to either 20 regularly or irregularly scheduled white-noise stimulations (4 min, 100 dBA). Blood was frequently sampled during the first and twentieth noise exposure, and during a reexposure after 24 hr. During the sampling periods, behavioral activities of the rats were recorded. The initial noise-induced CS release was partially reduced following the regular noise presentations. The increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
61
1
3

Year Published

1991
1991
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(72 citation statements)
references
References 38 publications
(47 reference statements)
5
61
1
3
Order By: Relevance
“…Our findings are in general agreement with an earlier study of de Boer et al [25] , where it was reported that following chronic predictable noise stress the corticosterone levels came to a stable level as compared to chronic unpredictable noise stress in rats. However our results differ from those of Fabiola et al [26] who reported more pronounced impairments after repeated restraint stress as compared to that seen after variable stress.…”
Section: Discussionsupporting
confidence: 94%
“…Our findings are in general agreement with an earlier study of de Boer et al [25] , where it was reported that following chronic predictable noise stress the corticosterone levels came to a stable level as compared to chronic unpredictable noise stress in rats. However our results differ from those of Fabiola et al [26] who reported more pronounced impairments after repeated restraint stress as compared to that seen after variable stress.…”
Section: Discussionsupporting
confidence: 94%
“…However, by increasing the days of exposure to stress the catecholamines' response may be adapted and therefore may cause the plasma glucose level on Day 30 not to change significantly (de Boer et al, 1990). It is noteworthy that the patterns of corticosterone and catecholamine of sympathoadrenal response and adaptation to intermittent stress are different (de Boer et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…1) Noise-stress was selected, since it has a high environmental and clinical relevance and appears to be a mild stressor with respect to neuroendocrine activation. 10) To determine the best potential impact of Triphala intake on an immune response, the highly immunogenic, non-infectious SRBC used as a stimulating agent in Values are expressed as mean ± S.D. of six animals.…”
Section: Resultsmentioning
confidence: 99%